Clinical psychology - Davey, Graham; Lake, Nick (Clinical psychologist); Whittington, Adrian (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Clinical Psychology, Third Edition offers an introduction to clinical psychology as it is operating on the ground - delivering clinical interventions, supervision, consultation, leadership, training and research, in rapidly changing health and care services. This new edition of Clinical Psychology brings together practitioners, researchers, and people who have used the services of clinical psychologists to explain how clinical psychologists work, the evidence that their work is based on, and how it can change peoples' lives for the better. The book explains the core principles of clinical practice, as well as outlines the role of a clinical psychologist within a healthcare team. It covers issues involved in working with children and families, adult mental health problems, people with disabilities and physical health issues, and the use of neuropsychology. In this fully revised third edition, every chapter has been brought up to date with developments in research and practice, and chapters have been added regarding the important fields of working with autistic people and working with people in forensic mental health services. Given the popularity of clinical psychology for many undergraduate and graduate students, the contents of this text have been designed around teaching and learning features that can be used as the basis for an intermediate or advanced-level course that will allow students to learn both breadth and depth about clinical psychology"--
Preface -- Part I. What is clinical psychology? -- 1. What does a clinical psychologist do? -- 2. The art and science of psychological practice -- 3. Working in teams: Different professions, different models of care and the role of the clinical psychologist -- Part II. Working with children and families -- 4. Working with children and young people -- 5. Working with families -- Part III. Working with adults in psychological difficulty -- 6. Working with depression -- 7. Working with people with anxiety disorders -- 8. Working with people with psychosis -- 9. Working with people with personality disorders -- 10. Working with people with eating disorders -- 11. Working with people with PTSD -- 12. Working with people in forensic mental health services -- Part IV. Working with people with disabilities and physical health problems -- 13. Working with people with intellectual disabilities -- 14. Working with autistic people -- 15. Working with people with physical health problems -- 16. Working with people with dementia -- 17. Working in neuropsychology -- Part V. Current professional issues in clinical psychology -- 18. Clinical psychology: Past, present, future -- 19. Moving forward into clinical psychology -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Clinical psychology; PSYCHOLOGY / General; PSYCHOLOGY / Applied Psychology; PSYCHOLOGY / Clinical Psychology